2006
DOI: 10.1029/2005jd006659
|View full text |Cite
|
Sign up to set email alerts
|

Emissions from the laboratory combustion of wildland fuels: Particle morphology and size

Abstract: [1] The morphology of particles emitted by wildland fires contributes to their physical and chemical properties but is rarely determined. As part of a study at the USFS Fire Sciences Laboratory (FSL) investigating properties of particulate matter emitted by fires, we studied the size, morphology, and microstructure of particles emitted from the combustion of eight different wildland fuels (i.e., sagebrush, poplar wood, ponderosa pine wood, ponderosa pine needles, white pine needles, tundra cores, and two grass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
229
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 208 publications
(267 citation statements)
references
References 45 publications
(86 reference statements)
24
229
2
Order By: Relevance
“…Pósfai et al (2003Pósfai et al ( , 2004 named this kind of particles as tar balls, a distinct carbonaceous particle type from soot. Tar balls originate from biomass burning, especially during smouldering burning conditions (Pósfai et al, 2003(Pósfai et al, , 2004Chakrabarty et al, 2006). The relative proportion of the tar balls remained quite low or moderate (1-4% tar balls) during the pollution episode compared with the proportion observed at some other sites (Pósfai et al, 2003;Pósfai et al, 2004;Hand et al, 2005).…”
Section: Tar Ballsmentioning
confidence: 99%
“…Pósfai et al (2003Pósfai et al ( , 2004 named this kind of particles as tar balls, a distinct carbonaceous particle type from soot. Tar balls originate from biomass burning, especially during smouldering burning conditions (Pósfai et al, 2003(Pósfai et al, , 2004Chakrabarty et al, 2006). The relative proportion of the tar balls remained quite low or moderate (1-4% tar balls) during the pollution episode compared with the proportion observed at some other sites (Pósfai et al, 2003;Pósfai et al, 2004;Hand et al, 2005).…”
Section: Tar Ballsmentioning
confidence: 99%
“…Aerosol size measuring instruments (such as Scanning Mobility Particle Size Spectrometer) have repeatedly shown that a lognormal size distribution is a good fit for realistic BC size distributions (Bond et al, 2002;Chakrabarty et al, 10 2006;Reddington et al, 2013;Wang et al, 2015), and it is also widely used in numerical calculations of BC radiative properties and forcing (Moffet and Prather, 2009;Chung et al, 2012;Li et a., 2016). Observations for BC have shown equivalent volume diameters from 0.01µm up to 1.0µm (Chakrabarty et al, 2006;Reddington et al, 2013;Wang et al, 2015). To describe a lognormal size distribution, a mean size and a standard deviation are needed.…”
Section: Bc Size Distributionmentioning
confidence: 99%
“…2. Soot carbon is composed of primary spherules with radii R p 0.025 µm that are aggregated with other spherules into large particles, and the resulting agglomerates look like chains of spheres with multiple branches (hence the term "chain aggregates;" Li et al, 2003a, b;Wentzel et al, 2003;Chakrabarty et al, 2006;Adachi et al, 2010;Wu et al, 2012;Chakrabarty et al, 2013). The absorption cross section for the aggregated particles can be reasonably modeled as a collection of the primary sC spheres, even though the agglomerates have complex shapes (Mulholland et al, 1994;Fuller, 1995;Farias et al, 1996;Fuller et al, 1999;Sorensen, 2001;Schnaiter et al, 2003;Chakrabarty et al, 2007;Liu et al, 2008;Chung et al, 2012a).…”
Section: Aae For Spectrally Invariant Kmentioning
confidence: 99%